Pengimbuhan Minyak Jagung Terproteksi dengan Berbagai Level Protein Ransum Sapi Friesian Holstein Meningkatkan Kadar Asam Lemak Tidak Jenuh Susu - Suhendra, Danes; Sudjatmogo, Sudjatmogo; Widiyanto, Widiyanto (Jurnal Veteriner; Vol 19 No 1 (2018)DO - 10.19087/jveteriner.2018.19.1.100, 2018)
This study was aimed to examine level supplemenation of corn oil (CO) as a source of protected poly unsaturated fatty acids (PUFA) and various crude protein (CP) levels in diets to ruminal iodin number and milk fatty acids of Friesian Holstein. The research done through two stages, using in vivo method and in vivo method. The corn oil protection is performed by saponification using KOH and then tranformed using CaCl2 to calcium salt. Research use two treatment factors with three replications, the first factor was supplementation of PUFA (L) with details L0 (Without protection), L1 (supplementation 75% Protected CO), and L2 (Supplementation 80% Protected CO) and the second factor is the P1 crude protein level (CP 12%) and P2 (CP 16%). The results showed that there was no interaction effect between the supplementation of protected CO with protein level to the ruminal iodin number, saturated fatty acid (SFA), unsaturated fatty acid (UFA), linoleic acid (LA), monounsaturated fatty acids (MUFA) and polyunsaturated fatty acid (PUFA) milk. The parameters are iodin number and milk fatty acids. Result of this research show that supplementation of protected CO increased the ruminal iodin number (P<0.01), UFA (P=), LA (P=) and milk PUFA (P=). Supplementation protected CO decrease milk SFA (P=). It can be concluded that supplementation of protected CO increases milk UFA of FH.
Keywords: susu, asam lemak, asam linoleat, minyak jagung